DESAIN LAPANGAN PAMEDAN AHMAD YANI SEBAGAI TAMAN KOTA TANJUNGPINANG BEBASIS KEBUDAYAAN MELAYU KEPULAUAN RIAU - Raharjo, Dhimas Setoyudho Anggoro; Hadi, Akhmad Arifin (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
Green Open Space was an instrument to provide an open space for people to do some activities that can be city icons. Pamedan Ahmad Yani Field was one of the city's icons in Tanjungpinang, but the design has not implemented the local culture into its design. Local culture can be used or implemented as a site appeal. This research aims to provide a redesign of Pamedan Ahmad Yani Field as a city park using local culture in the site design. Riau Islands culture was adapted considering the site location located in Tanjungpinang, Riau Islands, which is popular with its culture and literature, Gurindam 12. Questionnaires were distributed to 93 people to gain visitors' data and their perspectives about redesigning using local culture in the site design. The concept applied in the design is Modern-Local Cultural (Moltural), which combines local culture with current design developments. This research contains a series of designs consisting of commissioning, analysis, problem definition, conceptual studies, preliminary/schematic designs, site plans, and construction documents, with the final result in the form of designs with a local cultural approach consisting of working drawings and illustrations.